A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann) - Wosiacki, Wolmar B. (Zootaxa, 2005)
Trichomycterus guaraquessaba, new species, from an isolated small river of the Eastern Basin, Guaraqueçaba, south Brazil, is described, and T. iheringi is redescribed based on type material. No uniquely derived features were found in T. guaraquessaba that is distinguished from its congeners from south and southeastern Brazil by the combination of several morphological characters. No uniquely derived features were found in T. iheringi that is distinguished from its congeners from south and southeastern Brazil by the combination of several morphological characters. Putative relationships and shared characters are discussed for both species and ecological notes for T. guaraquessaba are presented.